Self-organization in manufacturing systems: challenges and opportunities - Leitão, Paulo (2010)
The current need for flexibility, re-configurability and robustness are crucial reasons for moving to new distributed manufacturing paradigms. Approaches that inherit biological concepts, such as Holonic Manufacturing Systems and Reconfigurable Manufacturing Systems, address this challenge. The self-organization concept offers an alternative way of designing adaptive systems, in which autonomy, emergence and distributed functioning replace preprogramming and centralized control. This paper discusses the benefits that bio-inspired theories can bring to the manufacturing world, and analyzes why in spite of their promising perspective their adoption by industry is extremely rare.